Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/1531-8249(200012)48:6<826::aid-ana2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent hyperpolarization and conduction block in chronic inflammatory demyelinating polyneuropathy

Abstract: Voluntary activity produces activity‐dependent hyperpolarization of the active motor axons. The present study investigated whether this hyperpolarization produces conduction block in chronic inflammatory demyelinating polyneuropathy (CIDP). Studies were performed in 10 healthy control subjects, 7 patients with CIDP, and 3 patients with multifocal motor neuropathy. The compound muscle action potential (CMAP) of the abductor pollicis brevis was recorded in response to supramaximal stimuli to the median nerve at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 11 publications
(6 reference statements)
3
32
1
1
Order By: Relevance
“…Patients with MMN also did not differ from normals, except for 1 ms-SRC ratio. These results confirmed previous studies showing nearly (but not "strictly") normal excitability profiles in territories unaffected by conduction blocks in MMN [27,28].…”
Section: Baseline Evaluationsupporting
confidence: 92%
“…Patients with MMN also did not differ from normals, except for 1 ms-SRC ratio. These results confirmed previous studies showing nearly (but not "strictly") normal excitability profiles in territories unaffected by conduction blocks in MMN [27,28].…”
Section: Baseline Evaluationsupporting
confidence: 92%
“…Activity-dependent hyperpolarization may, however, impair conduction in demyelinated axons (Bostock and Grafe, 1985;Kiernan et al, 1996a). Demyelinated motor axons are especially prone to activitydependent conduction block (Cappelen-Smith et al, 2000, 2003Kaji et al, 2000) as they express less inward rectification than sensory axons Kiernan et al, 2004;Lin et al, 2002). Reducing Na + /K + pump activity improves conduction in demyelinated axons in experimental (Kaji and Sumner, 1989a,b) and clinical trials (Kaji et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of excitability changes are different from those in chronic inflammatory demyelinating polyneuropathy (CIDP); previous reports on CIDP have shown that compared with normal subjects, strength-duration time constant was significantly shorter, and in the recovery cycle, CIDP patients had less refractoriness, supernormality and late subnormality than healthy controls (Cappelen-Smith et al, 2000;Sung et al, 2004). Current-threshold relationships did not show significant changes.…”
Section: Discussionmentioning
confidence: 72%